2005
DOI: 10.1159/000085441
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Epoietinum Therapy on the Oxidative Stress in Haemodialysis Patients

Abstract: Background: The causes of oxidative stress in haemodialysis (HD) patients are still controversial. Beside the uraemic state and dialysis-related factors, adjuvant drug therapies such as epoietinum (rHuEpo) and intravenous iron were involved. Methods: Several parameters related to oxidative stress were assessed by spectrophotometry in stable HD patients, treated for at least 2 months with epoietinum (n = 14; mean dose = 97.7 ± 19.1 U/kg/week) or not (n = 15), none of them on iron therapy, and in 13 controls. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Many authors have reported that erythropoietin stimulating agents (ESAs) reduce OS in HD patients . In contrast, one study found that ESA treatment in maintenance HD patients failed to show any antioxidant effect despite anemia correction …”
Section: Hemodialysis Procedures and Osmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have reported that erythropoietin stimulating agents (ESAs) reduce OS in HD patients . In contrast, one study found that ESA treatment in maintenance HD patients failed to show any antioxidant effect despite anemia correction …”
Section: Hemodialysis Procedures and Osmentioning
confidence: 99%
“…48,[52][53][54] In contrast, one study found that ESA treatment in maintenance HD patients failed to show any antioxidant effect despite anemia correction. 55 Anemia management in HD patients usually includes treatment with iron supplementation. Intravenous (iv) infusion of iron sucrose appears to aggravate OS in CKD and HD patients.…”
Section: Anemia-erythropoietin and Iron Administrationmentioning
confidence: 99%
“…Oxidative stress has historically been defined as an imbalance between oxidant production and antioxidant defense . Hemodialysis (HD) patients have a higher oxidative state, which results in the reduction of total antioxidant capacity and increased inflammation . HD patients experience numerous complications such as atherosclerosis and malnutrition, which may partly result from excess reactive oxygen species and/or decreased antioxidant activity .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hemodialysis (HD) patients have a higher oxidative state, which results in the reduction of total antioxidant capacity and increased inflammation. [3][4][5][6] HD patients experience numerous complications such as atherosclerosis and malnutrition, which may partly result from excess reactive oxygen species and/or decreased antioxidant activity. [7][8][9][10][11][12][13] There is growing evidence from experimental and clinical studies that oxidative stress may be involved in the pathogenesis of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical reports have demonstrated the positive impact of ESA on OS status in HD patients [7,8] while other scientists have found no antioxidant effects of ESA [9,10].…”
Section: Original Papersmentioning
confidence: 99%